2014
DOI: 10.2310/8000.2013.131243
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasonography adoption in Canada: using diffusion theory and the Evaluation Tool for Ultrasound skills Development and Education (ETUDE)

Abstract: Objective: Point-of-care ultrasonography (PoCUS) first appeared in the 1980s in North America, but the extent of the diffusion of its adoption is unknown. We characterized early PoCUS adoption by emergency physicians in Canada and its barriers to use using Rogers' diffusion of innovations theory. Methods: We developed a questionnaire based on a pilot study and literature review to assess past, current, and potential use of PoCUS and potential barriers to adoption. A Dillman technique for electronic surveys was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Other studies have also shown this, suggesting that male physicians are more likely to be early adopters of ultrasound [9,17]. Noteworthy, one study found that females felt they required more training compared to males to start using POCUS [18]. Similar examples can be found elsewhere in the adoption of technology [19].…”
Section: Discussionmentioning
confidence: 57%
“…Other studies have also shown this, suggesting that male physicians are more likely to be early adopters of ultrasound [9,17]. Noteworthy, one study found that females felt they required more training compared to males to start using POCUS [18]. Similar examples can be found elsewhere in the adoption of technology [19].…”
Section: Discussionmentioning
confidence: 57%
“…With lower patient volume, rural physicians may not have the opportunity to obtain competency in the learned skills or maintain them over time. 20 CEUS and other PoCUS certifying courses, such as EDTU and ECCU, require at least 50 determinate scans in each of the four domains of focused assessment with sonography in trauma (FAST), subxiphoid cardiac view for pericardial effusion, transabdominal scan for abdominal aortic aneurysm, and pelvic scan for confirming intrauterine pregnancy. Physicians must then complete visual, written, and practical exams to achieve independent practitioner (IP) status.…”
Section: Inability To Maintain Skillsmentioning
confidence: 99%
“…Despite the clear benefits of POCUS usage and rapid expansion of its utility in the ED, Canadian adoption rates and attitudes toward this technology have not been recently assessed. A Canadian census of past, current, and projected POCUS usage, as well as barriers to adoption, was most recently performed by Woo et al in 2007 using the Canadian Association of Emergency Physicians (CAEP) survey distribution database [15]. They found the number of survey respondents who reported “always” using POCUS for the following Canadian Point of Care Ultrasound Society (CPOCUS) core applications was FAST 41.8%, basic cardiac assessment 30.0%, early pregnancy assessment 23.3%, and abdominal aortic aneurysm assessment (AAA) 30.7%.…”
Section: Introductionmentioning
confidence: 99%